APAKAH DIMENSI BRAND EQUITY MEMEDIASI PENGARUH SOURCE CREDIBLE ONLINE REVIEWS TERHADAP PURCHASE INTENTION? STUDI EMPIRIS PADA PRODUK SMARTPHONE SAMSUNG DI KALANGAN GENERASI MILENIAL - Dwi Ardhana Widodo; Ari Setiyaningrum (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This study aims to examine whether the dimensions of brand equity which include brand awareness, perceived value, brand personality, organizational association, and perceived quality can mediate the effect of source credible online reviews on the purchase intention of the millennial generation on Samsung smartphone products. The research was conducted through an online survey by distributing online questionnaires to 211 millennial generation respondents in Jabodetabek. Sampling was done by purposive sampling method. The model was tested using the SEM-PLS analysis tool with the smartPLS statistical software. The findings of this study indicate that brand awareness, brand personality, and perceived value are proven to mediate the effect of source credible online reviews on purchase intention. Organizational association and perceived quality are not proven to mediate the effect of source credible online reviews on purchase intention in this study